CO2 Dispersion after Combustion - Korinek, Tomas; Frana, Karel (Manufacturing Technology Journal, 2015)
This study deals with a numerical simulation of CO2 dispersion after combustion of Ethanol. Numerical simulations were carried out with Reynolds averaged Navier-Stokes (RANS) approach. The mixture fraction theory was used for modeling of combustion. There were tested k-ε and k-ω turbulent models. Results obtained from numerical simulations were compared with results from an experiment.
Keywords: CFD; indoor air quality; non-premix combustion; carbon dioxide; ethanol